Energy Efficiency Indicators About an Italian Representative Hollow Glass Plant - Dario Atzori; Claudia Bassano; Simone Tiozzo; Sandra Corasaniti; Angelo Spena (Energies)
In recent years, the European Union has actively advocated for decarbonising hard-to-abate industries, including the glass sector. Stakeholders in both glass manufacturing and the research community have collaborated to fulfil ambitious CO2 emission reduction objectives mandated by Brussels, in several ways. The initial strategic action to be undertaken involves reducing energy consumption through energy efficiency interventions; to achieve this goal, it is essential to be aware of own consumption indicators by comparing them with appropriate performance ones. There are not many updated references connected to real-world cases, nor are indicators specifically tied to individual phases of the production process available. After a brief presentation of the container glass sector, which is the most important subsector, in terms of production capacity in Italy and the EU and its production process, the manuscript describes a real and representative plant of the sector, which has made its data available anonymously. In this way, energy performance indices representative of a typical production of the sector have been defined: they are updated and more detailed than the ones available in the literature. This representation therefore constitutes a case study that is representative of the most common plant configuration in the hollow glass sector in the EU.